Pengujian Modul Monitor Radiasi Pada Sistem Pemantauan Pengangkutan Zat Radioaktif - Adi Abimanyu (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Radiation monitor system or widely known as surveymeter has been widely used to monitor the rate of radiation exposure by utilizing detector to detect radiation pulses generated by radioactive substances. This study focused on testing the radiation monitor module used in the system of monitoring the transport of radioactive substances. The stability of the module was tested by chi square test with a standard source of Cs-137 performed a total of 20 data measurement range test instrument is done by providing a standard pulse from the pulse generator with a frequency of 1 to 327 kHz frequency as a substitute source of radiation and cps conversion factor to mR / h is done by comparing the results of measurements with standard tools. From the results of this study, the value of testing the stability of the background count 15.54 and the count value with 19.76 sources and within the range of 11,7 ≤ c2≤ 27,2 So this system is acceptable and has been functioning properly. While the conversion factor cps to mR / hr is 0.058 mR / jam.cps so the range radiation module is 0.058 mR / hr up to 18.98960 R / hour.